Um estudo sobre a relação da adoção do método ágil SCRUM com a produtividade em equipes de desenvolvimento de software - Bellenzier, Marina (2017)
New technology deployment projects should understand the immediate impact this change has on the professionals involved in the work process. In the first months of a technological change, it is possible to identify a certain resistance and even some conflicts that affect the levels of productivity of the teams. The objective of this work was to understand the relation of productivity with the changes in the work characteristics of teams that begin to adopt the SCRUM agile method for software development and to propose practices that help to reduce the learning curve and to improve productivity. Through the understanding of the Tuckman model, which describes the five stages of a team development: formation, confusion / conflicts, normalization, performance, and disintegration, a case study was carried out with a team that started to adopt SCRUM and identified the relationship between productivity and the phases described by Tuckman. In this sense, a field research was necessary to find practices that could help teams to increase their productivity during the confusion phase described by Tuckman. Through the preparation of a preliminary proposal, and an it’s preliminary evaluation in a Focus Group activity, this research presents a proposal to use the OKR technique (Objectives and Key-Results) along with SCRUM with the objective of assisting software team development, to concentration in the phase of confusion / conflicts.